KEKUATAN PEMBUKTIAN PERJANJIAN ELEKTRONIK DALAM SENGKETA UTANG PIUTANG DI ERA DIGITALISASI - mumtaz, fajrul (Institut Agama Islam Negeri Fattahul Muluk Papua, 2025)
The advancement of information technology has significantly transformed contractual practices, including debt agreements, from conventional formats into digital forms. This study aims to analyze the evidentiary strength of electronic agreements in debt-related civil disputes under Indonesian private law. Using a normative juridical approach, this research examines relevant statutory regulations such as the Indonesian Civil Code (KUHPerdata), Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law) as amended by Law Number 19 of 2016, and Government Regulation Number 71 of 2019 on Electronic Systems and Transactions. Selected court decisions are also reviewed, including Decision No. 38/Pdt.G.S/2023/PN.Jkt.Sel, which accepted a WhatsApp agreement as valid evidence. The findings indicate that electronic contracts possess equal legal force to written agreements, provided they meet the essential validity requirements and adhere to the principle of non-repudiation. However, key challenges persist in proving the authenticity of the parties' identities and the integrity of the electronic systems employed. This research contributes to strengthening the normative discourse on the need for adaptive reform in evidentiary law to accommodate the growing digitalization of civil legal relations.